2000
DOI: 10.1379/1466-1268(2000)005<0337:aaccih>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against chaperonin CCT in human sera with rheumatic autoimmune diseases: comparison with antibodies against other Hsp60 family proteins

Abstract: Chaperonin CCT containing t-complex polypeptide 1 is a cytosolic molecular chaperone that assists in the folding of actin, tubulin, and other proteins and is a member of the 60-kDa heat shock protein (Hsp60) family. We examined antibody titers against human CCT and other Hsp60 family members in the sera of patients with rheumatic autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematodes, Sjögren syndrome, and mixed connective tissue disease. Autoantibody titers against not only human mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 47 publications
1
48
0
2
Order By: Relevance
“…[52][53][54][55] What we present here, in this work, is another, distinct aspect of Hsp60 involvement in pathogenesis. Our data pertain to a different mechanism in which Hsp60 does not act as autoantigen but as an immune-system signal factor that triggers components of the innate immune response, leading to inflammation rather than to antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55] What we present here, in this work, is another, distinct aspect of Hsp60 involvement in pathogenesis. Our data pertain to a different mechanism in which Hsp60 does not act as autoantigen but as an immune-system signal factor that triggers components of the innate immune response, leading to inflammation rather than to antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…In addition it has been recently demonstrated that association of Hsp70 with autoantigens at the dermoepidermal junction can trigger off the production of autoantibodies against Hsp in Mrl/Mplpr/lpr mice and in SLE patients (11,12). Such anti-Hsp production would result in a cross-reactivity to nuclear extractable autoantigens-complexed with Hsp, notwithstanding further investigations are necessary to clarify this hypothesis (13,14). Overall the pathogenic role of Hsp in the immunopathology of lupus skin is still under discussion (15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Sandwich enzyme-linked immunosorbent assay for determining HSP47 concentration Sandwich enzyme-linked immunosorbent assay for determining HSP47 concentration was carried out as described previously (Yokota et al 2000(Yokota et al , 2003. Serum levels of HSP47 were measured in all enrolled patients.…”
Section: Study Populationmentioning
confidence: 99%